2020
DOI: 10.3389/fnins.2020.00285
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the RNA Binding Protein TIA1 Exacerbates Neuroinflammation in Tauopathy

Abstract: Neuroinflammatory processes play an integral role in the exacerbation and progression of pathology in tauopathies, a class of neurodegenerative disease characterized by aggregation of hyperphosphorylated tau protein. The RNA binding protein (RBP) T-cell Intracellular Antigen 1 (TIA1) is an important regulator of the innate immune response in the periphery, dampening cytotoxic inflammation and apoptosis during cellular stress, however, its role in neuroinflammation is unknown. We have recently shown that TIA1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 163 publications
(299 reference statements)
0
19
0
Order By: Relevance
“…1 A). Since our goal was to map the unstressed TIA1-bound transcriptome during neurodevelopment, and it has been shown that the delivery of siRNA, shRNA molecules, or direct manipulation of TIA1 protein levels can trigger cellular stress response [ 23 , 24 ], we did not perform a parallel RIP-seq on TIA1 KD cells as a nonspecific antibody-binding control. Eliciting the stress response could significantly change the identities of mRNAs bound to the remaining TIA1 protein, make these cells not equivalent to the untransfected experimental RIP-seq set, and represent a confounding factor to discriminate neurodevelopmental from stress-induced co-eluted mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…1 A). Since our goal was to map the unstressed TIA1-bound transcriptome during neurodevelopment, and it has been shown that the delivery of siRNA, shRNA molecules, or direct manipulation of TIA1 protein levels can trigger cellular stress response [ 23 , 24 ], we did not perform a parallel RIP-seq on TIA1 KD cells as a nonspecific antibody-binding control. Eliciting the stress response could significantly change the identities of mRNAs bound to the remaining TIA1 protein, make these cells not equivalent to the untransfected experimental RIP-seq set, and represent a confounding factor to discriminate neurodevelopmental from stress-induced co-eluted mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we chose Tia1 from many miR-34a-5p targets to confirm its gene and protein expression and validate its direct interaction with miR-34a-5p. This is because Tia1 reduction increases detrimental inflammatory responses in different types of cells and tissues such as bone [ 44 ], endometrium [ 42 ], peritoneal macrophages [ 45 ], and the central nervous system during chronic stress [ 43 ]. It controls a large network of immune system genes with modulatory roles in synaptic plasticity and long-term memory, which may be involved in stress-related psychiatric conditions [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several online databases (TargetScan, miRanda, TarBase, miR2Disease, miRTarBase, miRecords, miRWalk) were used to analyze and predict the potential target genes of miR-34a-5p, one of the miRs that shows significant changes after irradiation. Tia1, one of the miR-34a-5p targets, was selected to further validate their direct interaction because down-regulation of Tia1 increases inflammatory response and chronic stress, which may prevent neurogenesis [ 42 , 43 , 44 , 45 ]. The luciferase reporter assay was based on the previous description [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“… Gene Ontology analysis of nuclear-encoded mitochondrial genes associated with human TIA1-iCLIP and PARCLIP database. ( A ) Venn diagrams displaying number of nuclear-encoded mitochondrial genes ( Homo sapiens ) MitoCarta 3.0) [ 48 ] and HeLa TIA1 iCLIP analysis [ 18 ]. ( B ) Venn diagrams displaying number of nuclear-encoded mitochondrial genes ( Homo sapiens ) MitoCarta 3.0) [ 49 ] and HEK293 TIA1 PARCLIP analysis [ 19 ].…”
Section: Figurementioning
confidence: 99%
“…Adult TIA1-KO mice show a mild-arthritis phenotype [ 14 ] and recapitulate several key features of chronic post-traumatic stress disorder in humans. This phenotype is observed predominantly in female mice [ 29 ], and TIA1 haploinsufficiency exacerbates neuroinflammation in tauopathy [ 31 , 48 ].…”
Section: Introductionmentioning
confidence: 99%